The effectiveness of exercise on recovery and clinical outcomes of soft tissue injuries of the leg, ankle, and foot: A systematic review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration. Issue 5 (October 2015) - Woitzik, Erin; Jacobs, Craig; Wong, Jessica J.; Côté, Pierre; Shearer, Heather M.; Randhawa, Kristi; Sutton, Deborah; Southerst, Danielle; Varatharajan, Sharanya; Brison, Robert J.; Yu, Hainan; van der Velde, Gabrielle; et al.
Abstract Introduction Soft tissue injuries of the leg, ankle, or foot are common and often treated by exercise. The purpose of this study was to determine the effectiveness of exercise for the management of soft tissue injuries of the leg, ankle, or foot. Methods A systematic review of the literature was conducted. We searched five databases from 1990 to 2015. Relevant articles were critically appraised using Scottish Intercollegiate Guidelines Network (SIGN) criteria. The evidence from studies with low risk of bias was synthesized using the best-evidence synthesis methodology. Results We screened 7946 articles. We critically appraised ten randomized trials and six had a low risk of bias. The evidence suggests that for recent lateral ankle sprain: 1) rehabilitation exercises initiated immediately post-injury are as effective as a similar program initiated one week post-injury; and 2) supervised progressive exercise plus education/advice and home exercise lead to similar outcomes as education/advice and home exercise. Eccentric exercises may be more effective than an AirHeel brace but less effective than acupuncture for Achilles tendinopathy of more than two months duration. Finally, for plantar heel pain, static stretching of the calf muscles and sham ultrasound lead to similar outcomes, while static plantar fascia stretching provides short-term benefits compared to shockwave therapy. Conclusions We found little evidence to support the use of early or supervised exercise interventions for lateral ankle sprains. Eccentric exercises may provide short-term benefits over a brace for persistent Achilles tendinopathy and plantar fascia stretching provides short-term benefits for plantar heel pain.